Mind Matters - Hilton, James L.; Perdue, Charles W. (Boston : Allyn and Bacon, 2000)
Helps students explore psychology with units devoted to history, methods, biopsychology, learning, memory, sensation, and perception. Each unit contains self-contained modules that cover'core' psychological concepts through a combination of text, graphics, humor, and activities. Learning is reinforced with rapid reviews after each topic and quizzes after each unit.
Title from disc surface
System requirements for Macintosh: 68040/66 processor; 16MB RAM; System 7 or greater; QuickTime (included); 8MB free hard disk space; 256 color monitor; double-speed CD-ROM drive (4x recommended).
System requirements for Windows: IBM or compatible with 486/66 processor or Pentium; 16MB RAM; Windows 3.1 (Windows 95 or Windows 98 recommended), or Win NT; QuickTime 2.12 (included); 8MB free hard drive space; SVGA card for 256 color display, 640 x 480; double-speed CD-ROM drive (4x recommended); 8-bit SoundBlaster or 100% compatible sound card (16-bit recommended); speakers or headset
Keywords: Psychology -- Software